PROFESSOR GERMÁN ARCINIEGAS Educator, essayist, culture researcher and ideologist of the student movements in Colombia (2012)
This research work is a study of Professor Germán Arciniegas and his thought, Founder of the Federation of Students of Colombia, who began the student movement in the 20s decade in the XX century. It stands out his activity as a student, diplomat, political, Secretary of Education, university professor, journalist and academic of Languages and History. He´s an essayist of great ideas, author of numerous works and articles that study the identity of Latin America and its relationship with the world.